DIALOG DAN KERJASAMA ANTAR UMAT BERAGAMA DI INDONESIA - Mohammad Adnan (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2020)
In the context of the nation and state, especially in this case as the Indonesian nation. It is fitting for all of us to try to knit together the strings of one another. If we look at the long history of the Indonesian nation, which stretches from Sabang to Merauke, the context is that the independence of this nation was not solely due to the struggle of one group and one group and even one religion. More than that, that the independence of the Indonesian nation cannot be separated from the participation of all the Indonesian blood. This was not limited by racial differences, in essence almost all the nation's children fought together against the invaders. However, togetherness like that today has begun to be eroded by the interests of certain groups so that inter-religious conflicts in Indonesia often surface as an inevitable part. Conflicts between religions in this context occur due to the lack of dialogical dialogue between adherents of one religion to another. For this reason, we can understand a comprehensive understanding of the concept of religion in Indonesia in the knitting ties of harmonization between religious communities when dialogue is built between religions.